Government Transparency During the COVID-19 Pandemic: Good Information Governance? - Jannah, Lina Miftahul; Sipahutar, Muhammad Yasin (KnE Social Sciences, 2022)
The Government is required to provide open access information to the public in cases such as when the COVID-19 pandemic occurred in Indonesia and affected many aspects of life. Transparency in the provision of public information is an important part of good governance. The Government must build trust by being open and transparent about the information. Transparency is key to the success of the response to the pandemic. This study aimed to explain the need for transparency, especially in public information disclosure, during the handling of the pandemic and after; the strategies that need to be carried out to realize good information governance; and the challenges faced. Qualitative methods were used with secondary data. We argue that adjusting the disclosure of information according to the elements of good governance must be followed by a policy of providing information that is integrated, systematic, accurate, and clear. Keywords: good information governance, government transparency, information, public policy